Sales Improvement Strategy of Jazahijab on Tiktok Shop: An Analysis of The Effectiveness of Live Streaming As A Marketing Medium - Nur Ali Muchtar (Riviera Publishing, 2025)
The rapid growth of TikTok Shop as a social commerce platform has reshaped consumer behavior, especially through the use of live streaming in online shopping. This study aims to analyze the effectiveness of JazaHijab's live streaming strategy in boosting sales on TikTok Shop. The research objectives include identifying the current strategy, examining the factors influencing consumer purchase decisions, and formulating an optimal live streaming strategy to increase engagement and conversion. Using a qualitative descriptive approach and the Gioia Method, the study collected data through observation, semi-structured interviews, and performance documentation across four TikTok Shop accounts. The analysis is supported by SWOT and TOWS frameworks to derive strategic recommendations. The findings reveal that live interactivity, promotion, and product information clarity are the most influential factors in driving consumer purchases. Responsive and engaging hosts foster trust and emotional connection, while exclusive time-limited promotions and detailed product presentations enhance perceived value and urgency. However, inconsistencies in content standardization, suboptimal feature utilization, and technical disruptions hinder performance across different accounts. The study concludes that a structured live streaming strategy—supported by content SOPs, enhanced host training, real-time product visuals, and promotional calendars—can significantly improve sales performance. These insights contribute to the growing literature on digital marketing and offer practical guidance for MSMEs in optimizing TikTok Shop as a sales channel.